Using ADDIE to Influence Teachers’ Critical Consciousness in a Science Education Courses - Brandon, Latanya (Innovations in Science Teacher Education, 2025)
In this article, I describe the development and implementation of a single-semester science education course for secondary education science and math majors. The innovation lies in how the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) instructional design model helped me create an additional learning space within a tightly packed traditional teacher preparation program. Drawing upon tenets of the Rightful Presence Framework, I structured the course and assignments to challenge teachers’ assumptions about the relevance of sociopolitical issues and connect them to classroom-based science teaching and learning. This paper describes how the ADDIE model was applied to course design and implementation to influence science teachers’ sociopolitical awareness and inform my thinking as program coordinator. While the ADDIE model supported the use of critical frameworks in course design, implementation of the design did not result in significant changes in teachers’ critical consciousness. These results indicate that factors such as the modality of the course or the initial stage of critical consciousness may also influence science and math teachers’ sociopolitical development.